Peningkatan Kemampuan Spasial Anak Usia 5-6 Tahun melalui Kegiatan Studi Wisata ke Kebun Kopi di TK DWP Nurul Huda Jabung Malang - Ifah Hidayah; Mochammad Ramli Akbar; Sarah Emanuel Haryono (Golden Age: Jurnal Pendidikan Anak Usia Dini, 2025)
This study aims to enhance the spatial abilities of children aged 5-6 years through educational field trips to a coffee plantation. The research employed a Classroom Action Research (CAR) approach conducted in two cycles, each consisting of the stages of planning, action implementation, observation, and reflection. The research subjects were Group B children at TK DWP Nurul Huda Jabung, Malang, with the researcher acting as the primary instrument as well as the implementer of the actions. The findings indicate a significant improvement in children’s spatial abilities, as reflected in their increased understanding of directional concepts, position, size, and spatial relationships among objects in the surrounding environment. The field trip activities provided authentic and contextual learning experiences that facilitated spatial exploration, visual observation, and active use of spatial language. In addition, these activities enhanced children’s enthusiasm and active participation in the learning process. Therefore, educational field trips to a coffee plantation are proven to be an effective and enjoyable learning method for developing early childhood spatial abilities.